Efeitos de florestas ripárias em restauração em ecossistemas de riachos tropicais numa paisagem agrícola - Libório, Rogério Aparecido (2017)
The conversion of natural areas to human activities in watersheds is the main cause of riparian forest degradation, which, consequently, decreases the integrity of aquatic ecosystems. Therefore, restoration of riparian forests has been recommended as the best strategy for the recovery of streams in watersheds deforested by land use and cover. In Brazil, projects of riparian forest restoration are still recent and little is known about their effects on adjacent streams ecosystems. This study evaluated the effects of riparian forest restoration on stream water quality and aquatic macroinvertebrate communities using the multiple spatial scales approach. Sampling was carried out using the field protocol developed by the Environmental Protection Agency of the United States of America (US-EPA). We compared streams with natural riparian forests, streams with riparian forests in restoration and streams with riparian zones covered by pasture or grasses. A 150m reach was defined in each stream, and measurements of the physical structure of habitats and water quality were made, as well as samples of aquatic macroinvertebrates. Land-use and cover of each stream sub-basin was carried out through an environmental characterization of the landscape. Riparian forest restoration did not affect stream water quality and biological diversity after 10 and 13 years of project implementation, suggesting that the recovery of tropical streams in response to riparian forest restoration may be slow in sub-basin heavily altered by human activities. The present study fills a knowledge gap on the effects of riparian restoration and suggests the need for further studies and long term evaluations integrating new riparian forest restoration projects in watersheds with different intensities of human degradation to better understand the effects of the implementation of these projects on the quality of stream water and aquatic communities.